Tourists’ lifestyle and foodservice tendencies in social media - Loureiro, S. M. C.; Ferreira, E.S. (The Routledge handbook of gastronomic tourism, 2021)
This chapter reviews the literature on gastronomy tourism and provides an overview of the most important characteristic features of the fieldwork methodology. It examines the influence of lifestyle changes and the effect that Web 2.0 had on gastronomic tourism. Although literature proposes a link between tourism and gastronomy, there is a need to deepen the understanding of the perspective and opinion of tourists as end users of activities related to culinary tourism. Tourists want to have new food experiences, local food, and traditions, but, they need to know what is healthy or less healthy. The foodservice market has been suffering a strong impact from Asian food. All over the world, international tourism flows and receipts have been consolidating their growing tendencies, becoming a major category of international trade in services and therefore providing a high relevance in stimulating economic growth. Taking into account the market transformations, foodservice market has adopted a more social responsibility and accountability in their daily procedures.